Characterization of calcium phosphate powders originating from Phyllacanthus imperialis and Trochidae Infundibulum concavus marine shells - OKTAR, FAİK NÜZHET (ELSEVIER SCIENCE BV, 2013)
The study reports the preparation and characterization of powders consisting of the different phases of calcium phosphates that were obtained from the naturally derived raw materials of sea-shell origins reacted with H3PO4. Species of sea origin, such as corals and nacres, attracted a special interest in bone tissue engineering area. Nacre shells are built up of calcium carbonate in aragonite form crystallized in an organic matrix. In this work two natural marine origin materials (shells of echinoderm Sputnik sea urchin - Phyllacanthus imperialis and Trochidae Infundibulum concavus mollusk) were involved in the developing powders of calcium phosphate based biomaterials (as raw materials for bone-scaffolds) by hotplate and ultrasound methods. Thermal analyses of the as-prepared materials were made for an assessment of the thermal behavior and heat treatment temperatures. Samples from both sea shells each of them prepared by the above mentioned methods were subjected to thermal treatments at 450 degrees C and 850 degrees C in order to evaluate the crystalline transformations of the calcium phosphate structures in the heating process. By X-ray diffraction analyses various calcium phosphate phases were identified. In Sputnik sea urchins originated samples were found predominantly brushite and calcite as a small secondary phase, while in Trochidae L concavus samples mainly monetite and HA phases were identified. Thermal treatment at 850 degrees C resulted flat-plate whitlockite crystals - beta-MgTCP [(Ca, Mg)(3) (PO4)(2)] for both samples regardless the preparation method (ultrasound or hotplate) or the targeted Ca/P molar ratio according with XRD patterns. Scanning electron microscopy and Fourier transformed infrared spectroscopy were involved more in the characterization of these materials and the good correlations of the results of these methods were made. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Sea urchins; Trochidae shells; Natural bioceramics; Hydroxyapatite; Whitlockite; Characterization; OSTEOBLASTS MAINTAINED INVITRO; BOVINE HYDROXYAPATITE; MECHANICAL-PROPERTIES; CELL-PROLIFERATION; PARTICLE-SIZE; NACRE; BONE; BIOCOMPATIBILITY; FIBROBLASTS; COMPOSITES